BCH codes for 5G wireless communication systems over multipath fading channel - Ghasan Ali Hussain; Lukman Audah (Institute of Advanced Engineering and Science, 2020)
Due to its large peak to average power ratio (PAPR) and high out of band emission (OOBE), OFDM doesn't meet the requirements of 5G services. Additionally, it supports only one type of waveform parameters in entire bandwidth. In contrast, f-OFDM is dividing the system's bandwidth into a number of subbands to support several waveform parameters based on various service scenarios. So, Filtered-OFDM (f-OFDM) is considered as a modern enabler of the flexible waveform to overcome the OFDM drawbacks while remaining its advantages as well as, to encounter the new challenges that faced 5G. Nonetheless, there is a trade-off among OOBE, PAPR and SNR performance. Meanwhile, channel coding technology is one of the most important issue in physical layer which is playing an essential role in order to achieve the reliability and latency. So, BCH code has been suggested in this paper for f-OFDM system to achieve the reliability of transmission information and thus improving BER performance over multipath fading channel. Whilst, BCH-LTE system is introduced as a baseline in this paper that using for comparison purpose with proposed system. Simulation results showed that the proposed BCH-f-OFDM system was significantly better than BCH-LTE system in terms of decreasing OOBE and achieving improving in BER performance. Although, PAPR levels was stilling high in proposed system due to the trade-off among OOBE, PAPR and SNR performance. However, the proposed system is considered a promising candidate to meet the requirements of 5G services because of its ability to solve two important issues in between three trade-offs'.